Invisible challenges: Exploring sexuality prejudice in Physical Education classes (Research, Society and Development, 2024)
Physical education is an essential subject in the school curriculum, designed to promote students' health, well-being and physical development. However, sexuality prejudice often persists within physical education classes. Therefore, this article aims to investigate the different aspects of sexuality prejudice in physical education classes, identifying its causes, impacts and possible intervention strategies to promote a more inclusive and respectful educational environment for all students. This is a narrative review and the searches were carried out in the following databases: Google Scholar and Scientific Electronic Library (Scielo). The inclusion of articles was based on studies that resulted in: articles in English, Portuguese and Spanish, from 2019 to 2024. Eight articles on physical education and sexuality were selected. The heteronormativity prevalent in the school environment often marginalizes and invisibilizes non-heterosexual identities, creating a hostile environment for those who do not conform to traditional expectations of gender and sexuality. Therefore, in order to combat sexuality prejudice in physical education classes, it is essential to promote an inclusive and sensitive approach to gender and sexuality issues. This includes deconstructing gender stereotypes, providing safe and welcoming spaces for all students and implementing education policies and programs that promote diversity and acceptance.